Status of dairying in Ethiopia and strategies for future development - Tedla, A.; Gebre-Meskel, T.; Gebre-Wold, A.; Yemane, B.; Chigaru, P. (Institute of Agricultural Research, 1991)
Examines past and current situations of dairying in Ethiopia; assesses the major socioeconomic, infrastructural and technical constraints against the improvement of dairying in the country, with particular reference to feed availability and quality, use of native pasture, feed legumes, fodder trees and agricultural by-products, reproductive inefficiency, breeds used and breeding policies, and animal health and diseases; and discusses on the various Development strategies which must be geared to the alleviation of the major constraints mentioned above and to the Development of dairy industry in Ethiopia.